2015
DOI: 10.1097/sap.0000000000000530
|View full text |Cite
|
Sign up to set email alerts
|

Professional Burnout Among Plastic Surgery Residents

Abstract: Almost one third of plastic surgery residents exhibited a high degree of burnout; the risks were increased by being in the early years of training, feeling dissatisfied with career plans, and working in units in which senior surgeons did not make weekly ward rounds and in which regular staff meetings, which offer the opportunity to discuss cases or problems with other professionals, were not scheduled. Burnout increases the risk of medical errors and suicide among residents. Therefore, we suggest that screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 23 publications
1
37
0
2
Order By: Relevance
“…6,12,13 Studies that show no relation between aging and burnout levels also exist. [14][15][16] In this study shows no difference between age groups in terms of job satisfaction. However, some studies reported an increase in job satisfaction as a result of increase of experience gained in the profession and compliance.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…6,12,13 Studies that show no relation between aging and burnout levels also exist. [14][15][16] In this study shows no difference between age groups in terms of job satisfaction. However, some studies reported an increase in job satisfaction as a result of increase of experience gained in the profession and compliance.…”
Section: Discussionmentioning
confidence: 78%
“…6 Studies in concert with ours showing no relationship between marital status and burnout also exist. [13][14][15]22,28 This result can be based on the socio-cultural difference in the society.…”
Section: -26mentioning
confidence: 99%
“…(9) Plastik cerrahi asistanları arasında tükenmişlik düzeyini %25 olarak bulunmuş ve eğitimin ilk yıllarında riskin daha fazla olduğu, dolayısıyle tıbbi hata yapma riskin de fazla olacağı bildirilmiştir (12). Ancak yine aynı çalışmada bu bulgulara rağmen %62,9 oranında kariyerlerinden memnuniyet gö-rülmüştür.…”
Section: Bulgularunclassified
“…Haftalık çalışma saatlerinin yoğunluğuna rağmen tükenmişlikle ilişkisi de gözlenmemiştir. Çözüm olarak olayın farkındalığının olması, sık personel toplantıları, kariyer planlarının daha net yapılması önerilmiştir (12).…”
Section: Bulgularunclassified
“…Practice-based stress and burnout is not limited to attending surgeons. A study by Chaput et al 14 in France found that 25% of plastic surgery residents had high depersonalization scores, 14% reported high-level emotional exhaustion and burnout scales, and 48% had a perceived low level of accomplishment. Interestingly, weekly ward rounds with a senior surgeon was identified as being protective against resident burnout due to limiting depersonalization and facilitating the promotion of personal accomplishment.…”
mentioning
confidence: 99%